Pengaruh Kualitas Pelayanan, Variasi Produk, Dan Islamic Store Atmosphere Tehadap Minat Beli Ulang Melalui Value Equity Sebagai Variabel Intervening - Winayaputra, Muhammad Iqbal Luqyanfalah; Trisnawati, Desi Putri (Jurnal Ilmiah Ekonomi Islam, 2024)
The Indonesian culinary business market is becoming increasingly competitive. Therefore, business owners need to understand the factors that influence consumers' repurchase intention. This research focuses on service quality, product variety, and islamic store atmosphere to understand their impact on value equity and repurchase intention. A quantitative approach was used for the study, with data collected through a survey of a sample of 200 consumers of SFA Steak & Resto Klodran. The data collection method was a questionnaire survey. Statistical analysis, including linear regression and mediation, was used to test the relationship between the variables under study. The results indicate service quality and product variety have a positive and significant effect on value equity, while the islamic store atmosphere has a positive but insignificant effect. Additionally, value equity has a positive and significant influence on repurchase intention. Value equity moderates the relationship between service quality and product variety with repurchase intention, but does not moderate the relationship between islamic store atmosphere and repurchase intention.